Feasibility Analysis of Distributed Power Control System for Cognitive Radio Networks - Anggun Fitrian Isnawati (Jurusan Teknik Elektro Universitas Andalas, 2022)
The need for an efficient transmit power is affected by the condition of user and power control methods used. User conditions that categorized in cognitive femtocell networks included in the category as distributed user, so it required a distributed power control (DPC). To be implemented in cognitive radio network (CRN) communication, the system must be feasible. The problem raised in this research regarding the feasibility of implementing the DPC system on the CR network To meet the feasible requirements, it is necessary to test the system's feasibility through testing the eigenvalues of the link gain matrix obtained and testing the non-negative power vector conditions. In this study, experiments were carried out on 2 schemes of the number of users, namely the scheme of 5 users and 10 users, to determine the power requirements of each user according to the channel distribution. The results obtained for both schemes show that the total eigenvalue of the link gain matrix for all channels is less than 1 and all users meet the non-negative power vector requirements. So it can be concluded that those two schemes are feasible to implement a distributed power control system. Furthermore, as more users use the channel and the closer the distance between users, the more power is consumed due to high interference, necessitating high power compensation in order to maintain the target of signal to interference and noise ratio (SINR).